Digestive Surgery Patterns in Rural Indonesia: Insights from Lampung Province - Satrio Sarwo Trengginas (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2025)
Introduction Digestive surgical conditions represent a significant portion of the global surgical burden, particularly impacting low- and middle-income countries (LMICs). However, epidemiological data detailing the specific patterns of digestive surgery in rural Indonesian healthcare settings remain scarce. Understanding these patterns is crucial for effective healthcare planning and resource allocation. Methods: A descriptive observational study was conducted retrospectively across three type D hospitals situated in Central and South Lampung, Indonesia. Data were collected from surgical records and patient registers spanning the period from January 2024 to February 2025. All patients undergoing digestive surgical procedures during this timeframe, for whom complete data were available, were included. Results: A total of 773 patients underwent digestive surgery during the study period. The patient cohort showed a male predominance (65.20%). The three most frequent surgical conditions encountered were hernia (n=274, 35.45%), hemorrhoids (n=148, 19.15%), and appendicitis (n=123, 15.91%). Inguinal hernia (82%) treated predominantly with herniorrhaphy (89%) was the leading hernia type, peaking in the 51–60 year age group. Internal hemorrhoids (86%), primarily grade III (45%), were most common, with a peak incidence in the 41–50 year age group. Acute appendicitis (92%) was more frequent in females (53.66%), with a mean age of approximately 27 years. Conclusion: Hernia, hemorrhoids, and appendicitis constitute the primary digestive surgical workload in the surveyed rural type D hospitals in Lampung province. These findings underscore the specific surgical needs within these limited-resource settings and highlight a critical need for comprehensive, nationwide studies encompassing diverse hospital types and including non-operative cases to inform Indonesian health policy.